Pressure and Temperature Bearing Capacities of Fuzzy-Ball Fluid - Yang, C.; Zheng, L.H. (Asian Journal of Chemistry, 2014)
Fuzzy-ball fluid with the microstructure of “one core, two layers, three membranes” is an ideal plugging material in drilling engineering because it can plug different-sized leak channels automatically and can be degraded within a certain time. However, pressure and temperature are both high in deep wells, while the bearing capacities of pressure and temperature for Fuzzy-ball fluid are still not known so far. In this study, experiments were conducted to evaluate the pressure and temperature bearing capacity of the Fuzzy-ball fluid. The results show that: (1) Fuzzy-ball fluid can plug the coal rock core under the driving pressure up to70 MPa; (2) Fuzzy-ball fluid can keep its rheological properties up to 150 ºC. Since Fuzzy-ball fluid can keep its excellent performance up to 70 MPa and 150 ºC, it could be used in the wells as deep as 5000 m or more.